2013
DOI: 10.1074/jbc.m113.453373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Trafficking Reveals a Novel Lysosomal Targeting Mechanism via Amyloid Precursor-like Protein 2 (APLP2)

Abstract: Background: PCSK9 functions to degrade the LDLR by a previously unknown lysosomal sorting mechanism.Results: Here, we discovered and characterized a novel, pH-dependent interaction between PCSK9 and the amyloid precursor-like protein 2 (APLP2).Conclusion: APLP2 plays an integral role in postendocytic PCSK9 lysosomal sorting.Significance: These findings provide key insights into the mechanism by which PCSK9 degrades LDLR and reveal a novel lysosomal transport complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 44 publications
(68 reference statements)
4
75
1
Order By: Relevance
“…Once released from the cell surface, sortilin does not influence PCSK9 activity 37) . Recently, two proteins were suggested to enhance PCSK9-mediated degradation of the LDL receptor: one is sortilin, which binds to PCSK9 in the trans-Golgi network and possibly facilitates its secretion 37) , and the other is amyloid precursor-like protein 2 (APLP2), which facilitates trafficking of the PCSK9-LDL receptor complex to endosomes/lysosomes 38) . However, Butkinaree et al 39) reported that PCSK9 enhanced LDL receptor degradation independent of sortilin or APLP2 ex vivo The present study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Once released from the cell surface, sortilin does not influence PCSK9 activity 37) . Recently, two proteins were suggested to enhance PCSK9-mediated degradation of the LDL receptor: one is sortilin, which binds to PCSK9 in the trans-Golgi network and possibly facilitates its secretion 37) , and the other is amyloid precursor-like protein 2 (APLP2), which facilitates trafficking of the PCSK9-LDL receptor complex to endosomes/lysosomes 38) . However, Butkinaree et al 39) reported that PCSK9 enhanced LDL receptor degradation independent of sortilin or APLP2 ex vivo The present study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…17 Nevertheless, because the cytosolic tail of the LDLR is not necessary for the sorting of the [PCSK9≡LDLR] complex to lysosomes, 44,55 this suggests that another protein must bind the luminal CHRD domain and that such protein X would also have a transmembrane domain and cytosolic tail linking motor proteins in the cytosol to direct the complex to lysosomes (Figure 1). 44 In that context, a recent report proposed that the amyloid precursor-like protein-2 (APLP-2) can bind the CHRD at the surface of cells and in endosomes, and that this [LDLR≡PCSK9≡APLP-2] tripartite complex is then targeted to lysosomes (Figure 2), 56 by a still undefined mechanism.…”
mentioning
confidence: 99%
“…PCSK9 was found to bind through its C-terminal domain to APLP2 at acidic pH, followed by transport to the lysosome. This CL pathway did not require binding of PCSK9 to the LDLR ( 34 ). However, when PCSK9 was bound to LDLR via its catalytic domain, it formed a bridge to APLP2, which facilitated LDLR transport to the lysosome.…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serummentioning
confidence: 94%
“…We can propose a mechanism which links PCSK9 accumulation to the more rapid CL of the antibodies based on the studies in DeVay and coworkers ( 34,35 ). These authors demonstrated that an anti-PCSK9 antibody was delivered to lysosomes for degradation by a specifi c pathway involved in PCSK9 CL.…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serummentioning
confidence: 99%
See 1 more Smart Citation